Effect of adipic acid as crosslinking agent in polyvinyl alcohol nanocellulose from rice straw biocomposites - Nur Adyla Bt Muhammad Yusof (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Studies were made to investigate the biodegradable polymers by adding natural polymers into non-degradable plastics material. Therefore in this research, an attempt was made by incorporating based natural polymer which is cellulose nanocrystal (CNC) into polyvinyl alcohol (PVA) matrix. This study also investigated the effect of adipic acid as crosslinking agent to PVA/CNC film with different CNC content. Rice straw was collected, grinded and sieved to 63 (So(Bm before alkaline treatment. Alkaline treatment was performed to purify the rice straw with 32 g sodium hydroxide (NaOH) for 4 hours at 80 C distilled water. Then, CNC were extracted by sulphuric acid hydrolysis at 45 C for 60 minutes, using 23.4 mL of H2SO4 (9.41 M) for each gram of CNC fiber. The CNC was characterized through Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy (SEM). The result showed that hemicellulose and lignin broke down after undergoes several pre-treatment. The PVA/CNC films were prepared by mold casting with different concentrations of CNC (0 %, 2 %, 6 %, 10 % by wt) and the addition of 5 wt % (0.1 g) of adipic acid (AA) to the respective concentrations. The tensile test (i.e., tensile strength, break elongation and young modulus), FTIR analysis and SEM were used to investigate the properties of these biocomposites films. The result of PVA/CNC/AA film showed higher tensile strength from 30.2 MPa to 41.4 MPa and elongation at break (Eb) from 192.4 % to 220.5 % compared to PVA/CNC film. The morphology of both films indicates rough and coarse surface. Thus, the presence of AA enhanced the properties of PVA/CNC biocomposites film.